Qualitative assessment: an alternative praxis for nursing - Ma. de los Ángeles Meraz Rosas; Marco Antonio Cardoso Gómez; Virginia Reyes Audiffred; Rosa María Ostiguín Meléndez (Universidad de Alicante, 2018)
Qualitative evaluation is a process that allows analyzing the characteristics and problems of the phenomenon to be evaluated from the perspective of the actors involved. It is done through a direct and continuous contact in the field of study, this allows to obtain an overview of the culture and the context where the object of study is located. Objective. To propose the qualitative evaluation as an alternative in the nursing praxis. Method. Theoretical-inductive documentary analysis. The inclusion criteria were related to the utility and controversy in the qualitative research-evaluation approaches, in addition to allowing us to support their benefit in the field of nursing. Exclusion criteria were based on eliminating the literature regarding the evaluation focused on administrative processes in nursing. Results and conclusions. It is considered that the qualitative evaluation is a scientific resource, that allows to know and to understand the subjective dimension of experiences and meanings, needs and expectations, among others, of the person in the act of caring; Also, based on this knowledge and understanding, allows the issuance of judgments on why and how the person lives the phenomenon, in order to improve praxis.